Response to Covid-19 and Political Space at the Local Level - Hossain, Abul; Habib, Ahsan (CenRaPS Journal of Social Sciences, 2022)
Considering the widespread concern on political participation and voting rights in Bangladesh, many think the local organizations, civil societies, and NGOs cannot contribute expectedly in favor of mass peoples' needs for over a decade. On the other hand, many explain political context as state policies, elections, political systems, and government perspectives. Given these contexts, we are using the term political space in this article as an analytical method to explore the role of civil societies and local level organizations and institutions in responding to problems that arise due to the Covid-19 pandemic. Using the ethnographic methodology, we have provided empirical data supporting the dynamics of locally-led initiatives to respond coronavirus epidemic. The study explores the political space that institutional and informal civil society can create locally and play a role in the welfare of its citizens even when a country or a society is subject to strict control over certain political conventions and activities.